A Lethal Case of Sphingomonas paucimobilis Bacteremia in an Immunocompromised Patient. (20th March 2016) - Hardjo Lugito, Nata Pratama; Cucunawangsih,; Kurniawan, Andree
Abstract : Sphingomonas paucimobilis is a yellow-pigmented, glucose nonfermenting, aerobic, Gram negative bacillus of low pathogenicity. This organism was found in the implantation of indwelling catheters, sterile intravenous fluid, or contaminated hospital environment such as tap and distilled water, nebulizer, ventilator, and hemodialysis device. A 55-year-old female was hospitalized for diabetic foot ulcer in the presence of multiple comorbidities: diabetes mellitus, colonic tuberculosis, end-stage renal disease, and indwelling catheters for central venous catheter and hemodialysis. The patient passed away on the 44th day of admission due to septic shock. The organism found on blood culture on the 29th day of admission was multidrug resistant S. paucimobilis . Severe infection and septic shock due to S. paucimobilis have been reported particularly in immunocompromised patients, but there has been only one reported case of death in a premature neonate with septic shock. This is the first reported lethal case of S. paucimobilis bacteremia in an adult patient.